First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi - Král, David; Hrůzová, Lucie; Lu, Yuanyuan; Bai, Ming (Zootaxa, 2017)
Two species of Glaresis Erichson, 1848 (Coleoptera: Glaresidae) are reported from China. Glaresis ordosensis new species from Inner Mongolia and Shaanxi is described and compared with the similar species G. orientalis Medvedev, 1976 and G. oxiana Semenov, 1892. Glaresis orientalis, previously known only from Mongolia, is recorded from China (Inner Mongolia), for the first time. A key for the identification of Middle and Central Asian species of Glaresis is provided.